P3_7 Charged particles in a magnetic field - an integrator - Sadler, Tommy; Bates, Ethan; Brewer, Lois; Smith, Kennedy (Physics Special Topics, 2022)
We investigate the accuracy of using a simple numerical integrator (Euler Method) to find how a charged particle moves in a magnetic field. We find that the error depends on the choice of time step, but is not negligible for even small values, as such it is probably not the best method for this.